Copper oxide nanoparticles in clonal micropropagation of red oak - Zakharova Olgae; Gusev Alexander; Strekalova Nataliya; Grigoriev Gregory; Chebotareva Svetlana; Baranchikov Peter; Kataranova Anna (BIO Web of Conferences)
Oak is an important tree species, playing a fundamental role in many forest ecosystems. Obtaining high-quality oak planting material is a actual issue in forest biotechnology. The most promising method for this, in vitro micropropagation, faces a number of problems that can be overcome using a nanobiotechnological approach. In our work, we obtained flaky copper oxide nanoparticles with a particle size of 50–200 nm in diameter and a thickness of 10–20 nm, which were used in the WPN medium at a concentration of 0.75, 1.5, 3, 6, and 15 μg L-1 at the stage of introducing the original red oak material into the in vitro tissue culture. The study demonstrated a dose-dependent antimicrobial effect: seedling sterility increased from 80% (+10% to the control) at 1.5 μg L-1 CuO to 100% at doses of 3 μg L-1 and higher. The maximum survival rate was observed at 3 μg L-1 – 43%, which is 23% higher than the control values. At the multiplication stage, nanoparticles significantly increased plant viability – twice as much in the variant with 3 μg L-1 CuO and 1.7 times when using nanoparticles and phytohormones. The combined use of nanoparticles and hormones increased the seedling height by 1.5 times and the number of additional shoots by 3 times. At the rooting stage, CuO nanoparticles did not show any rhizogenesis-stimulating effect. At the same time, phytohormones and nanoparticles stimulated root formation. At the adaptation stage, a fairly low percentage of surviving and adapted plants was observed in the control variant, while the addition of nanoparticles had a positive effect on plant adaptation. The number of surviving seedlings increased by 15%, the number of adapted ones by 10. Thus, our study showed the prospects of using CuO nanoparticles to improve the biotechnology of clonal micropropagation of red oak. In the future, these results can be used in breeding and obtaining high-quality planting material for this species.